2022
DOI: 10.7717/peerj.12883
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and functional characterization of CDPK gene family reveal their involvement in response to drought stress in Gossypium barbadense

Abstract: Background Calcium dependent protein kinases (CDPKs) are a class of important calcium signal sensing response proteins, which play an important regulatory role in response to abiotic stress. However, researchers have not been excavated CDPKs’ role in drought in sea-island cotton(Gossypium barbadense L. ‘H7124’). Results Eighty-four CDPK genes have been identified in G. barbadense. These GbCDPK genes are unevenly distributed on 26 chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…In Solanum habrochaites, 11 ShCDPK family members were found to have LTR element, and the expression of a set of ShCDPK genes changed to a certain extent under cold stress [39]. Similar results were also found in other plants, such as Gossypium barbadense [66] and Medicago truncatula [67]. Moreover, the expression of ten selected BjuCDPK genes was observably induced by cold stress based on qRT-PCR analysis (Figure 6B), further supporting the RNA-seq data.…”
Section: Discussionsupporting
confidence: 80%
“…In Solanum habrochaites, 11 ShCDPK family members were found to have LTR element, and the expression of a set of ShCDPK genes changed to a certain extent under cold stress [39]. Similar results were also found in other plants, such as Gossypium barbadense [66] and Medicago truncatula [67]. Moreover, the expression of ten selected BjuCDPK genes was observably induced by cold stress based on qRT-PCR analysis (Figure 6B), further supporting the RNA-seq data.…”
Section: Discussionsupporting
confidence: 80%
“…To investigate the roles of R-SNAREs in cotton drought resistance, GhVAMP72l was silenced using VIGS technology ( Shi and Zhu, 2022 ). The results showed that GhVAMP72l -silenced plants were more sensitive to drought stress than control plants ( Figures 6B, C ), indicating that the drought resistance of GhVAMP72l -silenced plants was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CDPKs are involved in regulating the response of various plants to environmental stress. Various environmental factors, such as drought and salt injury, can cause the differential expression of calcium-dependent protein kinase genes and the specific accumulation of their mRNAs ( Li et al, 2019 ; Crizel et al, 2020 ; Shi and Zhu, 2022 ). Combined with the transcriptome data in this study, it was found that the Ca 2+ /calmodulin-dependent EF-Hand protein kinase and calcium-dependent protein kinase-related genes were highly expressed in the roots of patchouli under the allelopathic effects of p-HBA, positively responding to this stress.…”
Section: Discussionmentioning
confidence: 99%